Penerapan Kaidah Fikih Tentang Niat “Al-Umūru bi Maqāṣidihā” Dalam Kasus Hukum Tindak Pidana Pembunuhan - armaya azmi (TAQNIN: Jurnal Syariah dan Hukum, 2019)
The discourse about “niat (intention)” is a fairly general study in the literature of Islamic studies, this is due to the urgency of the position of intention in human law. One of the principles of fiqh formulated about intention is "Al-Umūru bi Maqāṣidihā". This rule is the Asasiyah Rule (basic) in the discussion themes of Al-Qawa'id Al-Fiqhiyyah. So far, the study of intention is only focused on matters of worship such as salat, fasting, etc. In this article the author tries to actualize the application of the principles of fiqh in a criminal case of murder, about how the position of intent and its application in the crime of murder, how to prove intention in legal matters, and how the influence of intentions on the judge's decision. This article will also be juxtaposed with the application of the principles of fiqh about intentions towards criminal law cases in the perspective of Islamic law and criminal law, which turned out to have many conformities